Economic evaluation of the benefits of reducing acute cardiorespiratory morbidity associated with air pollution - Anis Aslam H; Manary Matthew P; Johnson F Reed; De Civita Paul; Stieb David M; Beveridge Robert C; Judek Stan (BMC, 2002)
Abstract Background Few assessments of the costs and benefits of reducing acute cardiorespiratory morbidity related to air pollution have employed a comprehensive, explicit approach to capturing the full societal value of reduced morbidity. Methods We used empirical data on the duration and severity of episodes of cardiorespiratory disease as inputs to complementary models of cost of treatment, lost productivity, and willingness to pay to avoid acute cardiorespiratory morbidity outcomes linked to air pollution in epidemiological studies. A Monte Carlo estimation procedure was utilized to propagate uncertainty in key inputs and model parameters. Results Valuation estimates ranged from $13 (1997, Canadian) (95% confidence interval, $0-28) for avoidance of an acute respiratory symptom day to $5,200 ($4,000-$6,400) for avoidance of a cardiac hospital admission. Cost of treatment accounted for the majority of the overall value of cardiac and respiratory hospital admissions as well as cardiac emergency department visits, while lost productivity generally represented a small proportion of overall value. Valuation estimates for days of restricted activity, asthma symptoms and acute respiratory symptoms were sensitive to alternative assumptions about level of activity restriction. As an example of the application of these values, we estimated that the observed decrease in particulate sulfate concentrations in Toronto between 1984 and 1999 resulted in annual benefits of $1.4 million (95% confidence interval $0.91-1.8 million) in relation to reduced emergency department visits and hospital admissions for cardiorespiratory disease. Conclusion Our approach to estimating the value of avoiding a range of acute morbidity effects of air pollution addresses a number of limitations of the current literature, and is applicable to future assessments of the benefits of improving air quality.